Reducing Subspaces of the Dual Truncated Toeplitz Operator. (3rd June 2018) - Hu, Yinyin; Deng, Jia; Yu, Tao; Liu, Liu; Lu, Yufeng
Abstract : We define the dual truncated Toeplitz operators and give some basic properties of them. In particular, spectrum and reducing subspaces of some special dual truncated Toeplitz operator are characterized.